2023
DOI: 10.1002/star.202200280
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and Comparison of Wet Milling Fractions of Export Commodity Corn Originating from Different International Geographical Locations

Abstract: Soft endosperm corn has evident characteristics suitable for wet milling but is susceptible to breakage and fracture during transportation. In this study the millability of commodity corn samples with different endosperm hardness originating from different international locations is compared, and its economic impact on corn importers for wet milling is discussed. The broken corn and foreign material (BCFM) for the soft endosperm US commodity corn ranges from 1.13% to 5.57% which is higher than other commodity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Previous studies have shown that soft maize can generate a greater starch content through wet milling. However, hard maize is better suited for dry milling and is commonly used to make low-starch products, such as pasta and maize flour [3]. Food-grade maize specifically used for dry grinding can be used to make cereal, baked goods, beer, and other daily items.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that soft maize can generate a greater starch content through wet milling. However, hard maize is better suited for dry milling and is commonly used to make low-starch products, such as pasta and maize flour [3]. Food-grade maize specifically used for dry grinding can be used to make cereal, baked goods, beer, and other daily items.…”
Section: Introductionmentioning
confidence: 99%